Use of design of experiments to optimize the production of microbial probiotic biofilms - Speranza, Barbara; Liso, Arcangelo; Corbo, Maria Rosaria (PeerJ, 2018)
Here, we describe the production of a probiotic biofilm through three intermediate steps: (1) measurement of the adhesion capacity of 15 probiotic strains to evaluate their tendency to form biofilm on different surfaces (stainless steel, glass, and polycarbonate); (2) evaluation of the effects of pH, temperature, cellular growth phase, agitation, and presence of surfactants on probiotic biofilm formation (BF) through the Design of Experiments (DoE) approach; (3) study of the effects of pH, temperature and surfactants concentration on probiotic BF using the Central Composite Design. Finally, we show that biofilms pre-formed by selected probiotics can delay the growth of pathogens, such as Listeria monocytogenes chosen as model organism. Among the tested strains, Bifidobacterium infantis DSM20088 and Lactobacillus reuteri DSM20016 were found to be as the probiotics able to ensure the greatest adhesion (over 6 Log CFU cm2) to the surfaces tested in a very short time (<24 h). Cellular growth phase and agitation of the medium were factors not affecting BF, pH exerted a very bland effect and a greater tendency to adhesion was observed when the temperature was about 30 °C. The results obtained in the last experimental phase suggest that our probiotic biofilms can be used as an efficient mean to delay the growth of L. monocytogenes: the λ phase length, in fact, was longer in samples containing probiotic biofilms (0.30–1.02 h) against 0.08 h observed in the control samples. A reduction of the maximum cell load was also observed (6.99–7.06 Log CFU mL−1 against about 8 Log CFU mL−1 observed in the control samples).
Keywords: Biofilm; Probiotic; Bifidobacteria; Lactobacilli; Positive biofilms